Personalised care for people with excessive alcohol use following an episode of self-harm: a mixed methods community case study in a psychiatric liaison team - Wigham, Sarah; Titchener, Elizabeth; Jackson, Katherine; Kaner, Eileen; Gilvarry, Eilish; O’Donnell, Amy (Frontiers in Psychiatry, 2025)
BackgroundExcessive alcohol use is common among people presenting to emergency departments with self-harm; however, this group face barriers accessing appropriate support. This study aimed to evaluate a rapid access personalised face-to-face service developed to address this gap and explore wider implementation opportunities.MethodsWe conducted a service evaluation with a mixed methods convergent design. An NHS data custodian extracted and anonymised electronic health records data prior to sharing with the research team for analysis using descriptive statistics and non-parametric tests. Qualitative semi-structured interviews were conducted with patients and clinicians and analysed thematically. Quantitative and qualitative data were integrated, and meta-inferences drawn.ResultsPatients accessing the service (n=68) were mostly female (61.8%), white (83.9%), mean age 35 years (range 19-69), and most experienced additional mental health conditions alongside excessive alcohol use. Preliminary exploratory calculations comparing baseline to follow-up Recovery Quality of Life (ReQoL-20) scores suggested positive change. Three themes were identified from interviews with patients (n=11) and clinicians (n=7): (1) what the service added: rapidly plugging a recognised care gap for people using alcohol excessively but who are non-dependent and have poor mental health (2) what worked well: tailored relational support that builds recovery positive social networks and personal coping strategies (3) what could be improved: opportunities/challenges to sustaining and scaling-up the service.ConclusionsThe findings contribute to an evidence gap in appropriate care for patients with excessive alcohol use, self-harm and poor mental health. Whilst limited to one service, the findings highlight what patients valued, opportunities for implementation in other contexts, and thus have relevance internationally.